AMBIGUIDADE E CONSEQUÊNCIAS FUTURAS DOS COMPORTAMENTOS ÉTICOS: ESTUDO INTERCULTURAL - Manuel Portugal Ferreira; Cláudia Frias Pinto; João Carvalho Santos; Fernando A. Ribeiro Serra (RAE: Revista de Administração de Empresas, 2013)
The ethicality of business behaviors has been under scrutiny with the recent financial scandals and corporate and employees’ practices. In this study, based on data collected by survey, we compare the ethical perceptions of Portuguese (N=109) and Brazilian (N=190) business students, given a set of scenarios presenting unethical business and commercial practices. The tests use two cultural dimensions: tolerance to ambiguity and anticipations of future consequences as predictors of ethical propensity. The results denote significant differences across countries on the three dimensions, and the Brazilian are more tolerant to ambiguity and more conscious of the future consequences of their acts but also more prone to unethical behaviors. The perspective of short term gains seems to override the ambiguity and the medium and long term risks entailed in unethical behaviors. We conclude with a broad discussion and avenues for future research.